Genome-wide association study for feed efficiency indicator traits in Nellore cattle considering genotype-by-environment interactions - Neto, João B. Silva [UNESP]; Brito, Luiz F.; Mota, Lucio Flavio M. [UNESP]; Magnabosco, Claudio U.; Baldi, Fernando [UNESP] (Frontiers, 2025)
Introduction: Feed efficiency is a key factor in animal production sustainability, directly affecting production costs, environmental efficiency, and farmer profitability. The inclusion of feeding efficiency traits in cattle breeding programs has occurred later than other species due to longer life cycles and the high costs associated with measuring feed intake. However, genomic selection has facilitated the inclusion of difficult-to-measure traits in selection schemes. Thus, understanding the genetic basis of feed efficiency, particularly under varying environmental conditions, is essential. Methods: This study aimed to identify genomic regions associated with dry matter intake (DMI) and residual feed intake (RFI) in Nellore cattle by performing a genome-wide association study (GWAS) based on single-step genomic reaction norm models that account for genotype-by-environment interactions (G×E). Phenotypic data from 23,170 young bulls and heifers were collected across 301 feed efficiency trials. Genomic windows explaining more than 1% of the total direct additive genetic variance were identified for both the intercept and slope components of the reaction norm for each trait. Results: For RFI, ten and eleven genomic windows explained more than 1% of the genetic variance for the intercept and slope, respectively. For DMI, 12 windows were identified for the intercept and 17 for the slope. Within these regions, Multiple protein-coding genes were annotated (RFI: 66 for intercept and 47 for slope; DMI: 107 for intercept and 109 for slope), which are involved in key biological processes such as insulin, leptin, glucose, protein, and lipid metabolism; energy balance; heat stress response; feeding behavior; digestion; and nutrient absorption. Discussion: The results highlight the functional diversity of genes involved in feed efficiency and their dynamic response to environmental variation. While certain genes remained central across environments, others were specifically important under more challenging conditions, emphasizing the role of G×E in regulating these traits. Furthermore, the magnitude and direction of SNP effects varied across environmental gradients, reinforcing the relevance of G×E. Consequently, genomic estimated breeding values for DMI and RFI also differed between environmental extremes. These findings underscore the adaptability of genetic networks to environmental changes and are essential for refining strategies to improve feed efficiency in Nellore cattle.